Adulthood and parental roles. A study from teenager´s perception - Eduardo Moreno, José (2007)
This document aimed to show the adult world and parental role performance from the young teenager´s perspective, taking into account several authors who characterize nowadays adults and parent as insecure and fearful of their children. The sample was composed by 975 adolescents, from both sexes Buenos Aires (Argentina) to whom it was administered the Argentine Loneliness Scale and the Argentine Scale of Child Perception of Parental Relationship. Among these results, by means of Multivariate Variance Analysis, the male adolescents got higher averages in mother and father perception of Autonomy and Lax Discipline (p= 0001), that is to say that they perceive both parents as more permissive than female teenagers do.